Wind Energy Resource Assessment and Feasibility Study of Wind Farm in Mustang - Ghimire, Mukesh; Poudel, Ram C.; Bhattarai, Nawraj; Luintel, Mahesh Chandra (Journal of the Institute of Engineering, 2011)
This study presents the wind energy resource assessment and financial analysis of a 15 MW proposed wind farm in Mustang for utility scale power generation. Hourly meteorological data at Kagbeni and Thini measured at 10 m and 20 m height from 2001 to 2005 have been analyzed and the annual average wind speed and power density 75 m above ground level at Kagbeni are 8.05 m/s and 851 W/m2 whereas the same for Thini is 6.99 m/s and 337 W/m2, respectively. WAsP analysis shows that the wind speed and wind power density in the study area (20 × 20 km2) varies from 2.72 m/s to 44.51 m/s and 0.23 kW/m2 to 173.27 kW/m2. Optimized layout of a 15 MW wind farm that is comprised of twenty-five S52 -600 kW turbines, developed by openWind software, yields annual gross energy 63.58 GWh, and net energy 41.66 GWh with a capacity factor of 31.68%. The economic analysis of the farm suggests that the unit energy cost is in the range of NRs 4.57 to NRs 6.10 under different energy availability scenarios when meeting the project MARR of 16.1%. Based on the results, it is apparent that the wind resources at Mustang are suitable for harnessing wind energy especially for the purpose of utility scale electricity generation. Site accessibility is a major challenging factor to establish a wind farm currently. Keywords: WAsP; OpenWind; Resource Assessment; Wind Farm; Feasibility Study DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5099 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 93-104 Uploaded Date: 20 July, 2011